Photocatalytic self-cleaning BiOCl / COF composite membrane as well as preparation method and application thereof

BiOCl and COF nanosheets are deposited on the polymer base film through vacuum suction filtration technology to form a photocatalytic self-cleaning BiOCl/COF composite film, solving the problems of high cost and pollution in the existing film preparation process, achieving efficient photocatalytic and self-cleaning effects, and the process is simple and environmentally friendly.

CN119746649AActive Publication Date: 2025-04-04JIANGNAN UNIV

Patent Information

Application Number
CN202510026876.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-04
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The existing preparation process of photocatalytic self-cleaning films has the problems of high costs and easy generation of waste and pollutants in the production process, making it difficult to achieve the goals of simple process, low cost and environmental protection in the production process.

Method used

BiOCl nanosheets and COF nanosheets were deposited on the surface of the polymer base film by vacuum suction filtration technology. The oxygen-containing groups in the COF nanosheets were used to improve the dispersion of BiOCl nanosheets, reduce disorderly stacking, and form heterostructures to enhance photocatalytic capabilities.

Benefits of technology

The photocatalytic self-cleaning BiOCl/COF composite film is prepared, with excellent permeability and separation performance, which can effectively degrade contaminants on the surface of the film, extend the service life of the film, and has a simple process, low cost and good environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746649A_ABST
    Figure CN119746649A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of membranes, in particular to a photocatalytic self-cleaning BiOCl / COF composite membrane as well as a preparation method and application thereof. BiOCl nanosheets and COF nanosheets with photocatalytic characteristics are synthesized respectively, the two nanosheets are deposited on the surface of a polymer substrate film through a vacuum filtration technology, and due to the fact that a large number of oxygen-containing groups in the COF nanosheets improve the dispersity of the bismuth oxychloride nanosheets through hydrogen-bond interaction, disordered stacking of BiOCl in the stacking process is reduced, and the photocatalytic performance of the BiOCl nanosheets is improved. The COF is added to assist the bismuth oxychloride nanosheets in forming an interlayer channel with a screening effect, and the two nanosheets form a heterostructure, so that the photocatalytic capability of the composite film is enhanced. The preparation method of the composite membrane is simple, and the composite membrane has good permeability to Evans blue, Congo red, rhodamine B and other dyes, has excellent photocatalytic self-cleaning ability, and can be applied to separation of organic wastewater generated in the printing and dyeing industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of membrane technology, and in particular to a photocatalytic self-cleaning BiOCl / COF composite membrane and a preparation method and application thereof. Background Art

[0002] With the rapid development of industry, water shortage and energy crisis have become the main problems faced by human society. Membrane separation technology has high separation efficiency and low energy consumption, and is widely used in the field of water treatment. Membrane separation technology inevitably faces membrane pollution during long-term filtration. The preparation of a membrane with photocatalytic self-cleaning ability can well alleviate the membrane pollution problem and extend the life of the separation membrane. The photocatalyst can be loaded onto the membrane surface through vapor deposition and sol-gel methods. However, the vapor deposition method has high cost, requires the use of professional equipment and materials, and is prone to pollutants; the sol-gel method is cumbersome and expensive. Although the above two processes can prepare separation membranes with photocatalytic self-cleaning properties, they have the disadvantages of high cost and easy generation of waste and pollutants during the production process. Therefore, it is necessary to develop a preparation method for a photocatalytic self-cleaning membrane with simple process, low cost and environmentally friendly production process. Summary of the invention

[0003] In order to solve the above problems, the present invention provides a photocatalytic self-cleaning BiOCl / COF composite film and a preparation method thereof. BiOCl nanosheets and COF nanosheets with photocatalytic properties are synthesized respectively, and the two nanosheets are deposited on the surface of a polymer substrate film by vacuum filtration technology. Due to the large number of oxygen-containing groups in the COF nanosheets, the dispersibility of the bismuth oxychloride nanosheets is improved through hydrogen bonding, and the disordered stacking of BiOCl is reduced during the stacking process. The addition of COF assists the BiOCl nanosheets to form interlayer channels with a screening effect, and the two nanosheets form a heterogeneous structure, thereby enhancing the photocatalytic ability of the composite film.

[0004] The present invention provides a method for preparing a photocatalytic self-cleaning BiOCl / COF composite film, comprising the following steps:

[0005] (1) preparing bismuth oxychloride nanosheets: mixing bismuth nitrate, polyvinyl pyrrolidone and ethylene glycol, stirring, then adding a chloride salt solution to the mixed solution, performing a hydrothermal reaction, and adding an appropriate amount of ultrapure water after centrifugal washing to prepare a bismuth oxychloride nanosheet dispersion;

[0006] (2) preparing covalent organic framework nanosheets: dissolving 2,5-diaminobenzenesulfonic acid and trialdehyde phloroglucinol in a dimethyl sulfoxide solution to obtain a 2,5-diaminobenzenesulfonic acid solution and a trialdehyde phloroglucinol solution, and adding the trialdehyde phloroglucinol solution dropwise to the 2,5-diaminobenzenesulfonic acid solution under stirring to obtain a mixed solution, and stirring for a certain period of time to obtain a COF dispersion;

[0007] (3) Preparation of BiOCl / COF composite membrane: Take appropriate amounts of bismuth oxychloride nanosheet dispersion and COF dispersion, add ultrapure water to dilute, and ultrasonically disperse. After ultrasonication, the resulting mixed dispersion is deposited on a polymer support substrate by vacuum filtration and dried to obtain a BiOCl / COF composite membrane.

[0008] In one embodiment of the present invention, in step (1), the chloride salt solution is one of saturated sodium chloride and potassium chloride salt solutions.

[0009] In one embodiment of the present invention, in step (1), the amount of bismuth nitrate, polyvinyl pyrrolidone and ethylene glycol is 465-505 mg: 380-420 mg: 14-25 mL.

[0010] In one embodiment of the present invention, in step (1), the concentration of the bismuth oxychloride nanosheet dispersion is 1-2 mg / mL.

[0011] In one embodiment of the present invention, in step (1), the hydrothermal reaction time is 3 to 12 hours, and the temperature is 160 to 180°C.

[0012] In one embodiment of the present invention, in step (2), the molar ratio of trialdehyde phloroglucinol to 2,5-diaminobenzenesulfonic acid is 1:1-3.

[0013] In one embodiment of the present invention, in step (2), the concentration of the COF dispersion is 1 to 1.5 mg / mL.

[0014] In one embodiment of the present invention, in step (2), the mixed solution is stirred for 1 to 3 days.

[0015] In one embodiment of the present invention, in step (3), the film is dried for 12 to 48 hours.

[0016] In one embodiment of the present invention, in step (3), the polymer support substrate is one of nylon membrane, PVDF membrane, PAN membrane, PSF membrane and PES membrane.

[0017] In one embodiment of the present invention, in step (3), the mass ratio of bismuth oxychloride nanosheets to COF is 1-5:0.05-0.25.

[0018] The present invention provides a photocatalytic self-cleaning BiOCl / COF composite film prepared by the method described above.

[0019] The present invention also provides application of the photocatalytic self-cleaning BiOCl / COF composite membrane in dye / water separation.

[0020] The beneficial effects of the present invention are:

[0021] (1) The present invention constructs a photocatalytic self-cleaning BiOCl / COF composite membrane through vacuum filtration. The composite membrane generates free radicals under light to degrade pollutants on the membrane surface, dredge the pore structure of the membrane, restore the flux of the membrane, and extend the service life of the membrane.

[0022] (2) The present invention constructs a BiOCl / COF heterojunction through vacuum filtration. The formation of the heterostructure improves the light absorption capacity, increases the electron transfer rate, and enhances the photocatalytic ability.

[0023] (3) The present invention constructs interlayer channels with screening dyes through COF-assisted dispersion of BiOCl nanosheets, thereby expanding the application scope of two-dimensional nanomaterials in separation membranes.

[0024] (4) The BiOCl / COF composite film with photocatalytic self-cleaning properties prepared by the present invention has easy-to-synthesize raw materials and a simple film-forming process, thus having certain cost advantages.

[0025] (5) The composite membrane prepared by the present invention has excellent permeation flux (~33.4L·m -2 ·h -1 bar -1 ) and separation performance (Congo red retention rate 97.8%), can be used to screen Evans blue dye / aqueous solution, Congo red dye / aqueous solution, Rhodamine B dye / aqueous solution, etc., and can be used to treat printing and dyeing wastewater; and after illumination, the flux recovery rate of the membrane is significantly increased from 61.9% to 97.6%, showing excellent anti-pollution performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope image of the BiOCl nanosheet prepared in Example 1 of the present invention;

[0027] Figure 2 This is a scanning electron microscope image of the COF nanosheet prepared in Example 1 of the present invention;

[0028] Figure 3 This is a scanning electron microscope image of the BiOCl / COF composite film prepared in Example 1 of the present invention;

[0029] Figure 4 The thickness variation diagram of BiOCl / COF composite films with different ratios prepared by the present invention;

[0030] Figure 5 The scanning electron microscope images of BiOCl nanosheets prepared at different hydrothermal times according to the present invention. DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0032] The reagents used in each embodiment of the present invention are as follows: sodium chloride (NaCl, 99.5%) was purchased from Sinopharm Chemical Reagent Co., Ltd., 2,5-diaminobenzenesulfonic acid and polyvinylpyrrolidone (PVP, 99.5%) were purchased from Beijing Inokai Technology Co., Ltd., bismuth nitrate pentahydrate (Bi(NO3)3·5H2O, 99%) and ethylene glycol (EG, 99.5%) were purchased from Shanghai Titan Technology Co., Ltd., and trialdehyde phloroglucinol (TFP, 98%) was purchased from Jilin Zhongkeshen Technology Co., Ltd.

[0033] The porous support membrane used in each embodiment of the present invention is a polyethersulfone ultrafiltration membrane (PES, 0.2 μm) produced by Jinteng Experimental Equipment Co., Ltd.

[0034] Example 1

[0035] (1) Preparation of bismuth oxychloride nanosheets: 0.486 g of bismuth nitrate and 0.4 g of polyvinyl pyrrolidone were accurately weighed and dissolved in 25 mL of ethylene glycol solution. After stirring for 30 min, 10 mL of saturated sodium chloride aqueous solution was added dropwise (1 mL / min). After stirring for another 30 min, the mixed solution was poured into a 50 mL reactor liner, subjected to hydrothermal reaction at 160 ° C for 9 h, centrifuged and washed, and the lower precipitate was removed. After drying in an oven at 60 ° C, BiOCl nanosheets were obtained. The BiOCl nanosheets were dispersed in ultrapure water to obtain a bismuth oxychloride nanosheet dispersion with a concentration of 1 mg / mL.

[0036] (2) Preparation of covalent organic framework nanosheets: 8.53 mg of 2,5-diaminobenzenesulfonic acid and 6.3 mg of trialdehyde phloroglucinol were dissolved in 5 mL of dimethyl sulfoxide solution respectively. The trialdehyde phloroglucinol solution was added dropwise to the 2,5-diaminobenzenesulfonic acid solution under stirring at 100 rpm. The mixed solution was then gently stirred for 24 h to obtain a COF dispersion.

[0037] (3) Preparation of bismuth oxychloride / covalent organic framework composite membrane: Take 4 mL of BiOCl nanosheet dispersion with a concentration of 1 mg / mL, 0.1 mL of COF dispersion with a concentration of 1.5 mg / mL, add 200 mL of ultrapure water to prepare a mixed dispersion, deposit the nanosheets on the PES polymer substrate by vacuum filtration, and dry at 45°C for 24 h to obtain a BiOCl / COF composite membrane.

[0038] Comparative Example 1

[0039] The amount of COF added in step (3) was adjusted to 0, as shown in Table 1, and the remaining implementation conditions were the same as in Example 1.

[0040] Embodiments 2 to 5

[0041] The amounts of COF added in step (3) were adjusted to 0.05, 0.1, 0.2, and 0.25 mg, respectively, as shown in Table 1. The remaining implementation conditions were the same as in Example 1.

[0042] Test Example 1

[0043] The photocatalytic self-cleaning BiOCl / COF composite membrane prepared in Examples 1 to 5 and Comparative Example 1 was tested for permeation flux and retention rate by a dead-end filtration device. The specific test process is as follows: the test membrane is placed in a dead-end filtration device, an ultrapure aqueous solution is added to the device, and a pressure of 2 bar is used for pre-pressure for 1 hour. After the permeation flux of the membrane is stable, the permeation flux of the membrane is tested using a pressure of 1 bar, and then a 50 ppm dye solution is added to the dead-end device. After the solution permeates 10 mL (to avoid adsorption of the membrane), an appropriate amount of exudate is taken, and the absorbance change of the solution is tested by a UV-visible spectrophotometer to calculate the retention rate. The results are shown in Table 1.

[0044] Table 1 Permeation flux and Congo red rejection of photocatalytic self-cleaning BiOCl / COF composite membranes prepared in Examples 1 to 5 and Comparative Example 1

[0045]

[0046] From the data in Table 1, it can be seen that as the relative addition ratio of COF increases, the interlayer channels of the separation membrane become more regular, such as Figure 4 As shown in the figure, with the increase of COF loading, the thickness of the composite membrane does not increase but decreases, which also confirms the orderly assembly of the nanosheets. The rejection rate of the composite membrane for Congo red / water solution gradually increases, and due to the limitation of the trade-off effect, the permeation flux of the separation membrane gradually decreases.

[0047] Embodiments 6 to 9

[0048] The amount of BiOCl added in step (1) was adjusted as shown in Table 2, and the other implementation conditions were the same as in Example 1.

[0049] Test Example 2

[0050] The photocatalytic self-cleaning BiOCl / COF composite films prepared in Examples 6 to 9 were tested. The results are shown in Table 2.

[0051] Table 2 Permeation flux and Congo red rejection of photocatalytic self-cleaning BiOCl / COF composite membranes prepared in Examples 6 to 9

[0052]

[0053]

[0054] It can be seen from the data in Table 2 that with the increase of BiOCl addition, the regularity of the interlayer channels of the separation membrane becomes higher, which gives the membrane a gradually increasing dye retention rate. However, due to the limitation of the trade-off effect, the permeation flux of the separation membrane shows a downward trend.

[0055] Embodiments 10 to 12

[0056] The hydrothermal time of BiOCl in step (1) was adjusted (as shown in Table 3), and the remaining implementation conditions were the same as in Example 1.

[0057] Test Example 3

[0058] The photocatalytic self-cleaning BiOCl / COF composite films prepared in Examples 10 to 12 were tested. The results are shown in Table 3.

[0059] Table 3 Permeation flux and Congo red rejection of photocatalytic self-cleaning BiOCl / COF composite membranes prepared in Examples 10 to 12

[0060]

[0061] From the data in Table 3, it can be seen that with the increase of the hydrothermal time of BiOCl nanosheets, the permeation flux of the corresponding membrane gradually increases, and the retention rate shows a downward trend. It is speculated that the reason may be that the extension of the hydrothermal time makes the size of the BiOCl nanosheets larger. Due to the poor dispersibility of BiOCl nanosheets in water, the excessive sheet size is not conducive to the auxiliary dispersion of COF nanosheets through hydrogen bonding. The stacking of nanosheets is no longer orderly. The disordered stacking during the assembly process increases the permeation flux of the membrane and correspondingly reduces the retention rate of the membrane.

[0062] Take the photocatalytic self-cleaning membrane prepared in Example 1 and change the cleaning conditions after the membrane is contaminated.

[0063] The self-cleaning performance of the photocatalytic self-cleaning BiOCl / COF composite membrane prepared in Example 1 was tested. In three cycle experiments, the membrane was first subjected to a pure water flux test for 0.5 h, then a simulated pollutant (soybean oil) was added, the membrane was subjected to a flux test for 1 h, the membrane surface was illuminated for 2 h, and then a pure water flux test was performed for 0.5 h. This step was repeated three times, and the results are shown in Table 4.

[0064] Table 4 Long-term emulsion flux changes of different membrane samples prepared in Example 1

[0065]

[0066]

[0067] Due to the introduction of BiOCl and COF nanosheets with photocatalytic function on the membrane surface, after illumination, the flux recovery rate of the membrane was significantly increased from 61.9% to 97.6%, showing excellent anti-pollution performance.

[0068] Comparative Example 2

[0069] Omit BiOCl in step (3), and keep the other implementation conditions as in Example 1 to prepare a pure COF film.

[0070] BiOCl film, COF film, and BiOCl / COF film with the same loading amount were prepared and tested, and the results are shown in Table 5.

[0071] Table 5 Permeation flux and Congo red rejection of photocatalytic self-cleaning BiOCl / COF composite membrane prepared in Comparative Example 2

[0072]

[0073] It can be seen from the data in Table 5 that a single BiOCl membrane or COF membrane exhibits poor retention rate or too low permeation flux, while a small amount of COF nanosheets are added to the BiOCl dispersion to assist in dispersing the BiOCl nanosheets, making the bismuth oxychloride stacking more orderly and forming a complete screening channel. Compared with the pure COF membrane, the composite membrane exhibits good permeability.

[0074] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.

Claims

1. A method for preparing a photocatalytic self-cleaning bismuth oxychloride / covalent organic framework composite film, characterized in that: The following steps are involved: (1) mixing bismuth nitrate, polyvinyl pyrrolidone and ethylene glycol, adding a chloride salt solution, performing a hydrothermal reaction, and adding ultrapure water after centrifugal washing to obtain a bismuth oxychloride nanosheet dispersion; (2) dissolving 2,5-diaminobenzenesulfonic acid and trialdehyde phloroglucinol in a dimethyl sulfoxide solution to obtain a 2,5-diaminobenzenesulfonic acid solution and a trialdehyde phloroglucinol solution, and adding the trialdehyde phloroglucinol solution dropwise to the 2,5-diaminobenzenesulfonic acid solution to obtain a mixed solution, stirring the solution for a certain period of time, and obtaining a COF dispersion; (3) taking a bismuth oxychloride nanosheet dispersion and a COF dispersion, adding ultrapure water, and depositing the resulting mixed dispersion on a polymer support substrate by vacuum filtration after ultrasonication, and drying to obtain a BiOCl / COF composite film.

2. The method for preparing a photocatalytic self-cleaning bismuth oxychloride / covalent organic framework composite film according to claim 1, characterized in that: In step (1), the chloride salt solution is one of saturated sodium chloride and potassium chloride salt solutions; the hydrothermal reaction time is 3 to 12 hours, and the temperature is 160 to 180°C.

3. The method for preparing a photocatalytic self-cleaning bismuth oxychloride / covalent organic framework composite film according to claim 1, characterized in that: In step (1), the dosage of bismuth nitrate, polyvinyl pyrrolidone and ethylene glycol is 465-505 mg: 380-420 mg: 14-25 mL.

4. The method for preparing a photocatalytic self-cleaning bismuth oxychloride / covalent organic framework composite film according to claim 1, characterized in that: In step (1), the concentration of the bismuth oxychloride nanosheet dispersion is 1-2 mg / mL.

5. The method for preparing a photocatalytic self-cleaning bismuth oxychloride / covalent organic framework composite film according to claim 1, characterized in that: In step (2), the concentration of the COF dispersion is 1 to 1.5 mg / mL.

6. The method for preparing a photocatalytic self-cleaning bismuth oxychloride / covalent organic framework composite film according to claim 1, characterized in that: In step (2), the molar ratio of trialdehyde phloroglucinol to 2,5-diaminobenzenesulfonic acid is 1:1-3.

7. The method for preparing a photocatalytic self-cleaning bismuth oxychloride / covalent organic framework composite film according to claim 1, characterized in that: In step (3), the mass ratio of bismuth oxychloride nanosheets to COF is 1-5:0.05-0.

25.

8. The method for preparing a photocatalytic self-cleaning bismuth oxychloride / covalent organic framework composite film according to claim 1, characterized in that: In step (3), the polymer support substrate is one of nylon membrane, PVDF membrane, PAN membrane, PSF membrane and PES membrane.

9. A photocatalytic self-cleaning bismuth oxychloride / covalent organic framework composite film prepared by the method according to any one of claims 1 to 8.

10. Application of the photocatalytic self-cleaning bismuth oxychloride / covalent organic framework composite membrane according to claim 9 in the field of dye separation.

Citation Information

Patent Citations

  • Visible-light reaction polypyrrole / Bi2WO6 composite catalyst and preparation method thereof

    CN102941124A

  • Preparation method of three-dimensional-structure bismuth oxychloride @ bismuth oxybromide composite ultrathin nanosheet

    CN108722446A

  • Preparation method and application of BiOBr / COF composite photocatalyst

    CN111822055A

  • Double-layer COF / MXene composite membrane as well as preparation method and application thereof

    CN114272765A

  • Photocatalytic composite membrane as well as preparation method and application thereof

    CN114602552A

Cited By

  • BiOCl nanosheet doped PVDF composite membrane and preparation method thereof

    CN121550864A

  • Biocl nanosheet doped pvdf composite membrane and preparation method thereof

    CN121550864B